Biodegradation of remazol black b by bacterial consortium nar-2 - Kardi, Seyedeh Nazanin (2013)
The ability of the bacterial consortium NAR-2 consisting of A1, C1 and L17 to degrade the model azo dye Remazol Black B (RBB) was studied in batch and in continous systems. Continous decolourisation was performed in a borosilicate glass column (12 mm x 20 mm) packed with Surfactant Modified Clinoptilolite immobilised with bacterial consortium NAR-2. In batch studies, 90.79% decolourisation of RBB was achieved under microaerophilic condition within 80 minutes by inoculating 10% (v/v) of bacterial consortium NAR-2 at a 1:1:1 ratio. This was achieved in modified P5 medium pH 7 and incubated at 45°C under microaerophilic condition.In column bioreactor studies, decolourisation was observed at 45° and carried out by varying the flow rates and dye concentrations.Flow rate at 0.2, 0.4, 0.6 ,0.8 AND 1.0 ml/min were tested and dye concentration of 0.1, 0.3, 0.5, 0.7 and 1.0 g/L were used.Almost 95.8% decolourisation of 0.1 g/L RBB was achieved at the flow rate 0.2ml/min. By fixing 0.2 ml/min as default flow rate,varying concentrations of RBB were examined. Above 90% decolourisation was achieved with 0.1, 0.3 and 0.5 g/L RBB but at 0.7 and 1.0 g/L the percentage drop to 36 and 28%, respectively. Decolourisation percentage began to droped at higher dye concentration. Biomass leached out from the column was determined using viable cell count. From both flow rate and dye concentration experiments, it can be seen that C1 cell wash out was the highest as compared to A1 and L17. Analyses of decolourized and biodegradation products of RBB using total aromatic amines (TAA) showed that reduction of RBB resulted in the formation of aromatic amines. Further aerobic degradation for 15 days showed the amines concentration reduced from an initial of 18 mg/L to 2 mg/L following aerobic treatment in batch whereas in column experiment, the amines concentration dropped significantly from 34 mg/L to 11 mg/L.